Analisis Beban Pendinginan Produk Makanan Menggunakan Cold Box Mesin Pendingin LUCAS NULLE TYPE RCC2 - Topan Rombe Buntu; Frans Palobo Sappu; Benny Lokombanua Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2017)
Refrigeration machines have become an important necessity in modern society’s lifestyle. To optimize the use of a refrigeration machine, the cooling capacity of the refrigeration machine must conform to the heat load to be tackled. This research was aimed at analysing the cooling loads of several food products, that are eggplants, cucumbers, tomatoes, and beer by using the cold box of Lucas Nulle Type RCC2 refrigeration machine in Mechanical Engineering Laboratory of Sam Ratulangi University. The required data in this research were the mass and temperature of the food products, and also the electrical current. The value of each data was obtained from three time experiments where each experiment was conducted in 60 minutes. Data analysis, then, resulted the cooling loads and required power of each food product, as follows: for eggplants, the cooling load is 62.91 kJ with power of 241.23 Watt; cucumbers, cooling load 41.55 kJ, power 243.10 Watt; tomatoes, cooling load 60,36 kJ, power 235,62 Watt; and beer, cooling load 18,21 kJ, power 231,88 Watt. key word: cooling load, Refrigeration machines , LUCAS NULLE TYPE RCC2